Simple Bookkeeping and Determination of Cost of Goods Sold in the PKK Catfish Processing Group in Plaju Darat Village, Palembang City - Puri Pratami Ardina Ningrum; Novi Apriani; Muhamad Sidik; Sutarmo Iskandar; A.D. Murtado; Mukhtarudin Muchsiri; Nico Syahputra; Meika Puspita Sari (Altifani Journal: International Journal of Community Engagement, 2026)
The purpose of this community service activity is to improve the knowledge and skills of the PKK group mothers in Plaju Darat Village, Palembang City in conducting simple bookkeeping and determining the Cost of Goods Sold (COGS) for processed catfish products. The absence of systematic financial records and the determination of selling prices that are still based on estimates without considering the overall production costs are the main problems faced. Participatory Action Research (PAR) was used, using simple quantitative and qualitative approaches through observation, training, practice, and interactive discussion phases. This activity involved 20 participants, and evaluation was carried out through pre-tests and post-tests to measure the level of participants' understanding. The results of the activity showed a significant increase in understanding; the pre-test score increased by an average of 51.5 to 86, and the post-test score increased by an average of 34.5 points. Participants also showed improved skills in simple financial recording and calculating COGS. This activity increased participants' knowledge on how to manage business finances and determine reasonable selling prices. Therefore, the training in simple bookkeeping and COGS calculation has proven effective in improving the capabilities of catfish-based MSMEs.